Quality of red cells after combination of prion reduction and treatment with the intercept system for pathogen inactivation. Issue 3 (23rd March 2016) - Wiltshire, M.; Meli, A.; Schott, MA; Erickson, A.; Mufti, N.; Thomas, S.; Cardigan, R.
SUMMARY: Background and objectives: The pathogen inactivation (PI) INTERCEPT Blood System for Red Blood Cells utilises amustaline (S‐303) to inactivate a broad range of pathogens in red cell concentrates (RCC). The aim of this study was to investigate the effect on red cell quality of INTERCEPT treatment with and without prion reduction. Methods/materials: Five pools of five RCC each were prepared. These were split and treated as follows: (i) stored at 2–6 °C for 18 h, (ii) stored at 18–24 °C for 18 h, (iii) PI‐treated, (iv) PI‐treated then prion reduced and (v) prion reduced then PI‐treated. Prior to storage, PI‐treated RCC underwent an exchange step to remove S‐303 and other breakdown products. Components were tested throughout 35 days of storage for in vitro parameters of red cell quality. Results: All RCC met specification for volume and haemoglobin content. Haemolysis, microvesicle formation, supernatant potassium and deformability were lower and ATP levels higher in PI‐treated units when compared with control units. The effect of prion reduction in addition to PI treatment was minimal in all parameters tested except haemolysis, which was increased in units prion‐reduced after being PI‐treated. Conclusion: The PI‐treatment process did not increase red cell haemolysis or decrease ATP levels over storage. The lower haemolysis and supernatant potassium levels in treated RCC compared with control RCC were attributed to the exchange step. The effects of combining PI treatment and prion reduction were not more than additive when prion reduction precedes PI treatment.